PREVENTION OF THROMBOSES IN ANTIPHOSPHOLIPID SYNDROME - Lyubov Valeryevna Kondratyeva; T M Reshetnyak (Современная ревматология, 2009)
Warfarin and acetylsalicylic acid (ASA) are most frequently used to prevent thromboses of different localizations in general medical practice and in patients with antiphospholipid syndrome (APS). The mechanism of action of warfarin is associated with the ceased synthesis of blood coagulation factors VII, X, IX, and II. ASA inhibits platelet aggregation due to irreversible inactivation of СОХ 1. Patients with antiphospholipid (aPL) antibodies and venous thromboses need long-term moderate-intensity warfarin therapy. Patients with ischemic strokes without other indications for the use of anticoagulants may be given either warfarin or ASA. In the latter case, there is no need for laboratory control or an individual dose adjustment. The primary prevention of thromboses in the presence of aPL is also performed with ASA. When pregnancy occurs, women with obstetric manifestations of APS may be given small-dose ASA in combination with heparins. To reduce the risk of hemorrhages, warfarin dosage adjustment is initiated with the minimum doses (<5 mg/day). Novel ASA formulations, such as ASA with the unabsorbed antacid magnesium hydroxide, have been developed to prevent gastrointestinal tract complications.